Clinicopathologic associations of BRAF mutation status in patients with metastatic melanoma - Kwapisz, Dorota; Dansonka-Mieszkowska, Agnieszka; Switaj, Tomasz; Falkowski, Slawomir; Rutkowski, Piotr (European Journal of Oncology and Environmental Health, 2016)
Aim: BRAF is frequently mutated in cutaneous melanoma. The aim of the study was to assess BRAF status association with clinicopathologic features and outcome in patients with metastatic melanoma. Methods: We identified 197 consecutive Polish patients with metastatic melanoma treated in one oncological center and tested for BRAF mutation. We performed a retrospective chart review of patients to identify clinicopathologic characteristics in BRAF-mutant and BRAF wild-type patients. Results: 122/197 patients (61.9%) had BRAF mutation. The age at diagnosis of primary melanoma (PM) was significantly younger for BRAF-mutant (median age 52, n=122, range 19−78) than for BRAF wild-type (median age 58, n=75, range 19-85; p